Human Bocavirus: Can It Trigger Hemophagocytic Lymphohistiocytosis?. Issue 8 (November 2017) - Tanir Basaranoglu, Sevgen; Aykac, Kubra; Ozsurekci, Yasemin; Bajin, Inci; Tavil, Betul; Gumruk, Fatma; Ceyhan, Mehmet
Abstract : With improvements in molecular diagnostic methods, report of Human bocavirus (HBoV) as an etiologic agent in many studies on viral respiratory and gastrointestinal infections has been increasing. Two pediatric patients who presented with secondary hemophagocytic lymphohistiocytosis were examined for etiologic causes, including viruses. Whole bacterial and fungal cultures and viral serological studies were negative. Viral polymerase chain reaction of nasopharyngeal secretions showed HBoV. One was successfully treated with intravenous immunoglobulins, whereas the other died with multiorgan failure. Here we report 2 pediatric patients with secondary hemophagocytic lymphohistiocytosis and detection of HBoV as the sole agent, predicting an association.